Health and socio-economic status over the life course First results from SHARE Waves 6 and 7 - Börsch-Supan, Axel; Bristle, Johanna; Andersen-Ranberg, Karen; Brugiavini, Agar; Jusot, Florence; Litwin, Howard; Weber, Guglielmo (De Gruyter, 2019)
Health in later life is shaped by behavior and policies over the life course and reflects the differences between the societies in which we are ageing. This multidisciplinary book answers questions from all life course phases and its interconnections from a European perspective based on the most recent SHARE data.